The Anti-Smoking Ordinance as implemented in the City of Iloilo a policy analysis - Dayo, Ziny Baes
This study examines the dynamics behind and impact of two anti-smoking ordinances-- No.84 and No. 2002-225 in Iloilo City. This study aims to explain the factors that influence policy formulation and the effect of policy formulation on implementation of the ordinances banning smoking in public areas in the city., This study utilized the use of primary and secondary data. The researcher used Key Informant Interview as the primary data gathering mechanism. Through purposive sampling, 39 respondents-7 city councilors, 31 Volunteer Task Force Against Smoking were interviewed. The agenda setting, formulation and implementation stages are affected by the political behavior of the legislators and demands from pressure and interest groups. The political will of the sponsors as shown in their conviction and support led to the unanimous approval of the ordinance at the legislature. The content of the formulated ordinance affected the implementation process. The anti-smoking initiative receives strong media support and compliance from target groups.